2013
DOI: 10.1111/ijcp.12183
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke urinary incontinence

Abstract: Current evidence supports a thorough assessment to categorise the type and severity of post-stroke urinary incontinence. An individually tailored, structured management strategy to promote continence should be employed. This has been associated with better stroke outcomes and should be the aim of all stroke health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 46 publications
3
31
0
1
Order By: Relevance
“…Urinary dysfunction generally affects the quality of life in stroke survivors [6], but the development of UI following a stroke is also a predictor of future functional recovery after acute stroke [7], with a strong association with both increased mortality rates and poor functional outcomes [8]. As a result, clinicians and researchers have been highly interested in the management or treatment of poststroke UI.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urinary dysfunction generally affects the quality of life in stroke survivors [6], but the development of UI following a stroke is also a predictor of future functional recovery after acute stroke [7], with a strong association with both increased mortality rates and poor functional outcomes [8]. As a result, clinicians and researchers have been highly interested in the management or treatment of poststroke UI.…”
Section: Introductionmentioning
confidence: 99%
“…Recommended treatments for poststroke UI include bladder retraining, timed or prompted voiding, intermittent catheterization, the use of anticholinergic medications, and environmental and lifestyle support, none of which have sufficient evidence of efficacy, according to a systematic review [8]. Acupuncture therapies have been also explored for the management of UI after stroke in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary incontinence (UI) is a common problem after stroke (Kolominsky‐Rabas, Neundorfer, & Bernhard‐Heuschmann, ; Nakayama, Jørgensen, Pedersen, Raaschou, & Olsen, ; Tuong, Klausner, & Hampton, ; Williams, Srikanth, Bird, & Thrift, ), affecting at least 50% of stroke survivors. Although UI sometimes resolves rapidly and spontaneously, for many people it becomes a persistent problem, with up to a third of stroke survivors experiencing some degree of UI at 6 or 12 months (Mehdi, Birns, & Bhalla, ; Nakayama et al., ; Williams et al., ). UI is a strong predictor of mortality risk (John, Bardinic, Mégevand, & Combescure, ) and poor functional outcome after stroke (Mehdi et al., ; Meijer et al., ; Patel, Coshall, Rudd, & Wolfe, ).…”
Section: Introductionmentioning
confidence: 99%
“…Itoh et al recently showed that overactive bladder syndrome highly affected the quality of life of stroke patients, which was in turn associated with advanced age and male gender . Studies have been extensively performed on nocturia and incontinence; however, limited data are available on other storage symptoms in stroke patients, especially in Asian populations.…”
Section: Introductionmentioning
confidence: 99%